Managing a Case of a Congenital Cystic Eyeball: Case Report with Review of Literature - Aashish Raj Pant; Rinkal Suwal; Purushottam Joshi; Santosh Chaudhary (Case Reports in Ophthalmological Medicine)
A congenital cystic eyeball is an extremely rare condition, with only 52 cases reported in the literature to date. An orbital cyst replaces the eyeball which occurs due to the complete or partial failure in invagination of the primary optic vesicle during the fourth week of gestation. We discuss a case of a congenital cystic eyeball in a 14-year-old female who presented to us for a cosmetic blemish due to a large swelling in the right eyelid with the absence of a right eyeball since birth. She underwent removal of the cyst followed by an orbital implant and later prosthesis. Diagnosis of the congenital cystic eyeball was made based on the clinical and ultrasound B-scan features, intraoperative findings, and histopathology report. This article adds one more case to the existing literature on the congenital cystic eyeball. Orbital implant with prosthesis after excision of the cyst provided definitive diagnosis and a good cosmetic outcome in our case.